Decisões judiciais em casos de violência de gênero : o protocolo para julgamento com perspectiva de gênero como instrumento para mitigar ou eliminar as heurísticas e os vieses cognitivos - Lopes, Cristiano dos Anjos (2024)
The present study has as its central objective to address the historical, conceptual and empirical aspects that support all the logic behind human decision-making behavior by heuristics in cases that deal with gender issues, and how the Protocol for Judgment with a Gender Perspective contributes to the mitigation or elimination of cognitive biases resulting from decisions rendered by Direct Judges from the decision-making process by heuristics. Thus, the present research aimed to analyze, identify and discuss to what extent the Protocol of Judgment with Perspective and Gender could contribute to the mitigation and elimination of cognitive biases in judicial decisions involving issues of gender violence against women from the deductive method of research, that was exploratory, descriptive and analytical. For this, in the first chapter, we addressed the theoretical discussions that founded the development of new ways of envisioning the relationship between intuitive and deliberative thinking, Later, we will deal with the central aspects of this research work, initially addressing the conceptual aspects that involve the underworld of heuristics and cognitive biases. Subsequently, it was discussed the effects of heuristics in the decision-making process and judgment, according to the main exponents in the subject. Then, some of the main cognitive biases described by the specialized literature were presented, highlighting conceptual aspects and empirical research that give scientific support to the theories presented. In Chapter 2, we presented the incongruities from a gender perspective and the Brazilian legal landscape before the Maria da Penha Law. Soon after, the process of construction of the Maria da Penha Law was presented from a feminist point of view, highlighting the obstacles created by the concluding with a critical analysis on the role of the judiciary in combating gender violence and promoting equality between men and womenº. Already in Chapter 3, the Protocol of Trial with Gender Perspective of the National Council of Justice, its characteristics, organization and central aspects were discussed, as well as the type of response that this offers to decisions by heuristics in cases dealing with gender issues and their cognitive biases. Finally, the conclusions of this study were presented highlighting that the Protocol of Judgment with a Gender Perspective is an important tool for mitigation and elimination of cognitive biases in general and, in particular, for the representation bias, especially when compared with the quality of response offered to the other cognitive biases that were the subject of this research.